Intervenção religiosa na recuperação de dependentes de drogas Religious intervention and recovery from drug addiction - Zila van der Meer Sanchez; Solange Aparecida Nappo (Universidade de São Paulo, 2008)
OBJETIVO: Analisar intervenções religiosas emergentes para recuperação da dependência de drogas. PROCEDIMENTOS METODOLÓGICOS: Estudo qualitativo exploratório realizado em São Paulo, SP, em 2004 e 2005. Foram conduzidas 85 entrevistas em profundidade com ex-usuários de drogas que haviam utilizado recursos religiosos não-médicos para tratar a dependência de drogas e estavam abstinentes há pelo menos seis meses. Os grupos religiosos analisados foram católicos, evangélicos e espíritas. As entrevistas continham questões sobre dados sociodemográficos, religiosidade do entrevistado, história do consumo de drogas, tratamentos médicos para dependência de drogas, tratamento religioso e prevenção ao consumo de drogas pela religião. ANÁLISE DOS RESULTADOS: Houve diferenças no suporte ao dependente de drogas em cada grupo. Os evangélicos foram os que mais utilizaram a religião como forma exclusiva de tratamento, apresentando repulsa ao papel do médico e a qualquer tipo de tratamento farmacológico. Os espíritas foram os que buscaram mais apoio terapêutico à dependência de álcool, simultaneamente ao tratamento convencional, justificado pelo maior poder aquisitivo. Os católicos utilizaram mais a terapêutica religiosa exclusiva, mas relataram menos repulsa a um possível tratamento médico. A importância dada à oração como método ansiolítico era comum entre os três tratamentos. A confissão e o perdão - por meio da conversão (fé) ou das penitências, respectivamente para evangélicos e católicos - exercem apelo à reestruturação da vida e aumento da auto-estima. CONCLUSÕES: Segundo os entrevistados, o que os manteve na abstinência do consumo de drogas foi mais do que a fé religiosa. Contribuíram para isso o suporte, a pressão positiva e o acolhimento recebido no grupo, e a oferta de reestruturação da vida com o apoio incondicional dos líderes religiosos. OBJECTIVE: To analyze the role of emerging religious interventions in the recovery from drug addiction. METHODOLOGICAL PROCEDURES: An exploratory qualitative study carried out in the city of Sao Paulo, Southeastern Brazil, in 2004 and 2005. In-depth interviews were held with 85 former drug users who had turned to non-medical religious resources for the treatment of their drug addiction and who were free from drugs for at least six months. The religious groups included in the analysis were Catholics, Evangelicals and Spiritualists. The interviews contained questions relating to sociodemographic data, the religiosity of the interviewee, his or her history of drug consumption, medical treatment for drug addiction, religious treatment and prevention of drug consumption through religion. ANALYSIS OF RESULTS: There were differences between the religious groups in the way that the drug addict was supported. The group that most used religion as an exclusive form of treatment was the Evangelicals, who rejected the intervention of a doctor andr any kind of pharmacological treatment. The Spiritualists most turned to therapeutic support for alcohol dependence, as well as conventional treatment, on account of their greater purchasing power. Catholics generally relied exclusively on religious therapy, but were less likely to reject the possibility of medical treatment. The importance given to prayer as an anxiolytic method was common in the three treatments. Confessions and pardons - in the forms of (faith) conversions and penitence for Evangelicals and Catholics respectively - served to help to rebuild people's lives and restore their self-esteem. CONCLUSIONS: According to the interviewees, what helped them to maintain their abstinence from drugs was more than just religious faith. Other factors included the support, positive pressure and welcoming offered by the group, and the offer to rebuild their lives with the unconditional support of religious leaders.